Proteomic analysis of Fasciola gigantica excretory and secretory products (FgESPs) co-immunoprecipitated using a time course of infected buffalo sera - Zheng, Mengwei; Jiang, Xuelian; Kong, Xinping; Guo, Yanfeng; Zhang, Weiyu; Di, Wenda (Frontiers in Microbiology, 2022)
Widespread Fasciola gigantica infection in buffaloes has caused great economic losses in buffalo farming. Studies on F. gigantica excretory and secretory products (FgESP) have highlighted their importance in F. gigantica parasitism and their potential in vaccine development. Identifying FgESP components involved in F. gigantica-buffalo interactions during different periods is important for developing effective strategies against fasciolosis. Buffaloes were assigned to non-infection (n = 3, as control group) and infection (n = 3) groups. The infection group was orally administrated 250 metacercariae. Sera were collected at 3, 10, and 16 weeks post-infection (wpi) for the non-infection group and at 0 (pre-infection), 1, 3, 6, 8, 10, 13, and 16 wpi for the infection group. FgESP components interacting with sera from the non-infection and infection groups assay were pulled down by co-IP and identified using LC-MS/MS. Interacting FgESP components in infection group were subjected to Kyoto Encyclopedia of Genes and Genomes (KEGG) metabolic pathway and gene ontology (GO) functional annotation to infer their potential functions. Proteins of FgESP components identified in the non-infection group at 3, 10, and 16 wpi accounted for 80.5%, 84.3%, and 82.1% of all proteins identified in these 3 time points, respectively, indicating surroundings did not affect buffalo immune response during maintenance. 490 proteins were identified in the infection group, of which 87 were consistently identified at 7 time points. Following GO analysis showed that most of these 87 proteins were in biological processes, while KEGG analysis showed they mainly functioned in metabolism and cellular processing, some of which were thought to functions throughout the infection process. The numbers of specific interactors identified for each week were 1 (n = 12), 3 (n = 5), 6 (n = 8), 8 (n = 15), 10 (n = 23), 13 (n = 22), and 16 (n = 14) wpi, some of which were thought to functions in specific infection precess. This study screened the antigenic targets in FgESP during a dense time course over a long period. These findings may enhance the understanding of molecular F. gigantica-buffalo interactions and help identify new potential vaccine and drug target candidates.